First-principles calculations of the structural and electronic properties of AIN, GaN, InN, AIGaN and InGaN - Beloufa, Abbes; Bensaad, Zouaoui; Soudini, Bel-Abbes; Sekkal, Nadir; Bensaad, Abdelallah; Abid, Hamza (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008 & vol. 2; issue 1, 2009.